Clinical Presentation and Fetomaternal Consequences of Placental Abruption: A Multi-Center Study - Ayin, Noor ul; Saleem, Ali Saqlain; Fatima, Sharoona; Bashir, Hifza; Aziz, Ajwa Tariq; Tufail, Aneeza (Biological and Clinical Sciences Research Journal, 2025)
Placental abruption is a major obstetric morbidity described by early detachment of the placenta from the uterine wall. It is dangerous to the mother and fetus in cases of haemorrhage, fetal insufficiency, and perinatal mortality. The crucial issue in upgrading clinical management and minimizing adverse outcomes related to this condition is understanding the fetomaternal outcomes related to the condition. Objective: To evaluate the fetomaternal outcome of patients admitted with a placental abruption in a multi-centre environment. Methods: This was a cross-sectional study; the study was performed at Central Park Teaching Hospital, Lahore, from December 2022 to June 2023. Two hundred patients with ill conditions of placental abruption, and no earlier history of placental pathology development, were accepted. Departmental ultrasonographic scans and structured questionnaires were used in the collection of data. Maternal age, gestational age, kinds of abruption, heart rate of the baby, maternal complications, type of delivery, and neonatal outcome were reviewed utilising the SPSS program, version 25. Assessment of statistical significance was done using chi-square and independent t-tests. Results: The average age of the mothers was 29.4 +/- 5.7 years, and the average gestational age at which the mothers went to hospital was 34.2 +/- 3.1 weeks. Syndesmotic OGD presenting symptom was the most widespread, vaginal bleeding (78%), followed by abdominal pains (64%). Bad maternal conditions involved postpartum hemorrhage (32), hypovolemic shock (18), and emergency cesarean section (41). Fetal outcomes were intrauterine fetal death (22%), low birth weight (38%), and NICU hospitalisations (45%). A statistically strong linkage was identified amid heavy abruption and poor neonatal outcomes (p < 0.01). Conclusion: There is a high fetomaternal morbidity associated with pregnancy abruption. Fast identification of obstetric emergencies and urgent obstetric treatment are important to enhance maternal and fetal survival. The burden of this obstetric emergency can be decreased by means of multi-center surveillance and prescribed management protocols.